Formation of targets and investigation of Mn4Si7 coatings produced by magnetron sputtering - Б.Д. Игамов; Г.Т. Иманова; А.И. Камардин; И.Р. Бекпулатов (Қарағанды университетінің хабаршысы. Физика сериясы)
The morphology, composition, electrical and optical properties of bulk samples and vacuum coatings of Mn4Si7 obtained by magnetron sputtering on a SiO2/Si structure were studied. It is shown that manganese silicide coatings with a thickness of about 150 nm are close in properties to bulk Mn4Si7, have a uniform finegrained structure of a semiconductor nature, which is characterized by thermal sensitivity up to 20-30 μV per degree. In addition, this article presents the electrophysical properties of high manganese silicide films produced by the authors by magnetron sputtering method. Heated films Mn4Si7 -146 nm coating has a uniform structure with fine grains, due to sufficient coating density. Since Mn4Si7 nanoclusters are semiconductor materials, it can be assumed that there will be energy barriers for charge carriers at the nanocluster–amorphous phase interface separating this phase. An increase in thermal sensitivity from 0 μV/K to 20 μV/K up to 800 K is explained by the disappearance of energy barriers for charge carriers at the nanocluster–amorphous phase interface due to the ordering of nanoclusters. The change from 20 µV/K to 28 µV/K upon cooling is explained by the appearance of structural relaxation in the amorphous phase.